Numerical Simulation of Air Flow Field in Freezer - 徐斌; 胡振武; 王志远; 马志豪; 段雪涛; 侯子午; 刘建西 (Zhileng xuebao)
The inner channel flow fields in the belt freezer were calculated with the transmission belt moving by use of the PHOENICS code.The effects of the belt moving,the inlet air velcoity,different heights of channel and incidence angles on inner flow fields were analyzed.It is indicated that the moving of the transmission belt had no influence on the air velocity distribution along the transmission belt in normal working condition of the belt freezer.The selections of the inlet air velocity and heights of the channel should be considered synthetically of magnitudes, uniformities of air velocity and losses of air flow,and the best angle of incidence was zero.